Hubungan Indeks Massa Tubuh Terhadap Tekanan Darah Pada Lansia di Posbindu Klinyo Margoluwih Sleman - Nurhayati, Ummy Aisyah; Dameyla, Nindy Suci (Politeknik Kesehatan Kemenkes Mamuju, 2024)
Excessive fat in the body can cause the risk of obesity. To determine the condition of body fat, a simple measurement is using the Body Mass Index (BMI). The bigger the body mass, the bigger the volume of blood needed to supply oxygen and food to the tissues of body, thereby increasing blood pressure. Blood pressure is the force exerted by the walls of the arteries by pumping blood away from the heart. Increased blood pressure is also caused by age because entering old age will have a decrease in the cardiovascular system which causes increasing blood pressure. Observational analysis was with cross sectional design. The research sample was taken using a total sampling technique with number of samples 70 people. The research instrument used a digital scale, microtoise staturemeter and aneroid sphygmomanometer. Data analysis used univariate analysis and bivariate analysis, namely the Spearman correlation test. Spearman Rank correlation test showed that there was a significant relation between BMI and blood pressure in the elderly (r = 0.788, p = 0.000). There is a significant relationship between BMI and blood pressure where the increase in BMI is in line with the increase in blood pressure in the elderly.